The Influence Of Work Motivation And Incentives On Increasing Production - Lugu Nustiani; Mukhamad Kholil Aswan (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
This research was conducted at PT. Hesed Indonesia which aims to analyze and explain the influence of work motivation and incentives on increasing production which is experiencing unfavorable conditions including slow service to guests at The salaries or wages at PT Hesed Indonesia are not paid properly. Most of the security guards on duty are not very polite, sometimes they shout or scold, and the working hours system has delayed hours, that is, they work overtime without pay. Research data obtained through questionnaires and interviews. The sample used in this study was 93 respondents. The results of the research are expected to provide useful information for the management and guest satisfaction. The data obtained were processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis uses multiple regression analysis to determine the effect of independent variables on the dependent variable, model testing, hypothesis testing, and before carrying out these tests, validity and reliability tests are carried out first. The results of the regression analysis show that there is an increase in work motivation and incentives for increased production. This shows that to increase the production produced by employees, it is necessary to increase high work motivation and incentives that are in accordance with employee expectations.